Elvis and the underdogs - Lee, Jenny, 1971-; Light, Kelly, 1970- (New York, NY : Balzer + Bray, an imprint of HarperCollins Publishers, 2014)
All his life Benji, now ten, has been sickly and he has long been targeted by the school bully, but after a seizure Benji gets a therapy dog that is not only big enough to protect him, it can also talk.
School Library Journal starred, June 2013
Booklist starred, April 2013
Publisher's Weekly, April 2013
Horn Book, November 2013
4.7
3-6
Keywords: Service dogs -- Juvenile fiction; Dogs -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Sick -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Family life -- Juvenile fiction; Service dogs -- Fiction; Dogs -- Fiction; Human-animal communication -- Fiction; Sick -- Fiction; Bullies -- Fiction; Schools -- Fiction; Family life -- Fiction; Service dogs -- Fiction; Dogs -- Fiction; Human-animal communication -- Fiction; Sick -- Fiction; Bullies -- Fiction; School stories; Family life -- Fiction